The Impact of Financial Development on Carbon Emissions in Africa - Tsaurai, Kunofiwa (International Journal of Energy Economics and Policy, 2019)
The paper explored the influence of financial development on carbon emissions in West African countries using pooled ordinary least squares (OLS), fixed and random effects with data spanning from 2003 to 2014. On the theoretical front, arguments for both financial development led positive impact on carbon emissions and financial development led negative impact on carbon emissions are quite compelling. Empirical studies on the role played by financial development on carbon emissions produced quite divergent and conflicting findings. It is clear from both theoretical and empirical sides that the influence of financial development on carbon emissions is still a contentious issue which is yet to be resolved in literature. Overally, pooled OLS approach (both lagged and non-lagged variable) shows that only domestic credit provided by financial sector resulted in the significant increase in carbon emissions in Western African countries. Keywords: Financial Development; Carbon Emissions; Western African Countries JEL Classifications: E44; N27; Q5 DOI: https://doi.org/10.32479/ijeep.7073